Teknologi Pembuatan Garam Bersistem Elektrik Pada Kelompok Garam Meugah Raya - Sari, Dewi Maya; Fachri, Zoel; Zulfan, Zulfan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
This Stimulus Community Partnership Program (PKMS) aims to make an electric salt cooker that can be used by salt farmers efficiently. The process of making salt by the Meugah Raya Salt Group still uses the traditional method of evaporating seawater in plastered plots with sunlight without using any technological tools. Although raw materials are abundant, salinity and dissolved pollutants are very diverse. Moreover, the equipments used were still conventional and relies on firewood as a salt cooking fuel so that the capital needed to cook salt is large enough. To solve the current problem, through this program, it created an electrical system salt cooker named "Electrical Salt Machine". Meanwhile, the method employed started at the socialization and site survey, the finalization and design of tools, preparation of tools and materials, manufacturing tools, testing tools, evaluating and refining tools, simulating the use of tools to partners and assisting partners and monitoring. The results showed that the process of making salt by using this tool was able to save time at cooking salt. Furthermore, it was more efficient since it had no longer of using firewood so that it saved costs.